2002
DOI: 10.1046/j.1365-8711.2002.05121.x
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy colours in high-redshift, X-ray-selected clusters - I. Blue galaxy fractions in eight clusters

Abstract: We present initial results from a wide‐field, multicolour imaging project, designed to study galaxy evolution in X‐ray‐selected clusters at intermediate (z∼0.25) and high redshifts (z∼0.5). We give blue galaxy fractions from eight X‐ray‐selected clusters, drawn from a combined sample of three X‐ray surveys. We find that all the clusters exhibit excess blue galaxy populations over the numbers observed in local systems, although a large scatter is present in the results. We find no significant correlation of b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
56
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 66 publications
(148 reference statements)
16
56
2
Order By: Relevance
“…These results support the general view that blue galaxies dominate the galaxy population in the outskirts of clusters in contrast to the central cluster region (e.g., Ellingson et al 2001;Fairley et al 2002;Dahlén et al 2004;Tran et al 2005). They also imply that field galaxies, which are generally bluer than cluster galaxies (see, for example, Lewis et al 2002;McIntosh et al 2004), fall into the cluster environment, turn red (possibly via some process that truncates star formation), and that blue dwarf galaxies get preferentially disrupted or transformed into red dwarfs at small clustercentric radii.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These results support the general view that blue galaxies dominate the galaxy population in the outskirts of clusters in contrast to the central cluster region (e.g., Ellingson et al 2001;Fairley et al 2002;Dahlén et al 2004;Tran et al 2005). They also imply that field galaxies, which are generally bluer than cluster galaxies (see, for example, Lewis et al 2002;McIntosh et al 2004), fall into the cluster environment, turn red (possibly via some process that truncates star formation), and that blue dwarf galaxies get preferentially disrupted or transformed into red dwarfs at small clustercentric radii.…”
Section: Discussionsupporting
confidence: 88%
“…Transforming the magnitude limit utilized by Aguerri et al to our filter and distance scale (M R c ∼ −21), we find an 80% probability of a correlation. Our results are in agreement with Fairley et al (2002) and Wake et al (2005), who found no significant correlation between f b and L X .…”
Section: Blue Galaxy Fractionsupporting
confidence: 93%
See 1 more Smart Citation
“…3.3.1) is a consequence of our choice to define red and blue galaxies (see Fairley et al 2002 for an opposite result when using the red-sequence to split red and blue galaxies).…”
Section: Blue/red Definitionmentioning
confidence: 99%
“…However, observations of the near-infrared luminosity function show that any change with environment is likely to be small [68,69,70]. On the other hand, the strong redshift evolution observed in the colors of galaxies in both clusters [71,72,73] and the field [74,75] suggests that some galaxies transform from one population to another. In particular, Bell et al [18] noted a build up of stellar mass on the red sequence by a factor of about two between z ∼ 1 and 0, averaged over all environments.…”
Section: Transformation Modelingmentioning
confidence: 99%